Contested Ethnicities and Images: Studies in Acts and Arts - Balch, David L. (Wissenschaftliche Untersuchungen zum Neuen Testament, 2015)
Cover -- Preface -- Table of Contents -- Abbreviations -- Introduction -- Part One: Luke-Acts (Chapters 1-11) -- Part Two: Roman Domestic Art and the New Testament (Chapters 12-18) -- Part Three: Two Book Reviews (Chapters 19-20) -- Part One: Luke-Acts -- Chapter 1: The Contested Movements in Rome, Athens, and Jerusalem toward Citizenships/Memberships of Multiple Ethnicities (Introducing Chapters 2-11) -- 1. Will Romans, Greeks, Jews, and/or Christians Accept or Reject Citizenships/Memberships of Multiple Ethnicities? -- 1.1 Narratives and Deliberative Speeches Constructed by Dionysius concerning a Citizenship of Multiple Ethnicities -- 1.2 A century after Dionysius, Luke-Acts also urges readers/churches to acculturate the Roman practice of a membership of plural ethnicities -- 1.3 Social/political conflict around ethnicity is so common that Lucian can satirize it -- further, whether an ethnic group accepts other ethnic groups is contested and forms the basis of praising or criticizing other groups -- 2. Emma Dench and Andrew Wallace-Hadrill's Recent Studies of Changing Greco-Roman Ethnic Attitudes and Practices -- 3. Roman imperial, aggressive plural ethnicity challenges not only the Greek Dionysius, but also challenges early Jews and early Christians -- 4. Both Dionysius and the author of Luke-Acts reevaluate their traditions: what is the place of Athens/Jerusalem, and which ancient writers are most authoritative in the present, while living under Rome? -- 5. Postcolonial Interpretation: Will Those Conquered by Rome Acculturate by Changing their Languages, Customs, Laws, and Gods/ Goddesses? -- 5.1 Study of colonized Greeks under Rome and Contemporary Postcolonial Studies -- 5.2 Political, internal conflict around adapting languages/customs/ god(esse)s/laws in the Greek authors Dionysius and Luke-Acts in the Context of the Early Roman Empire